EVALUASI PEMILUKADA DALAM PERSPEKTIF ANGKA GOLPUT DI KECAMATAN GAMBIRAN TAHUN 2015 - Mahbub Junaidi (Jurnal Public Policy, 2016)
This research try to know and analyze the phenomenon of the white in gambiran on local election and deputy head of the banyuwangi district in 2015. Researchers are most interested in doing this research, with the implementation of the general election there are many people who did not vote (golput) during the election especially the in district gambiran. Given this situation, but this study tries to examine how the golput in kecamatan gambiran and faktor-faktor what sajakah affecting the emergence of golput in district gambiran in pemilhan regional leaders and deputy head of the district banyuwangi in 2015. A theory that used in clarifying these problems were behavioral therapy voters, factors affect voted (golput), and concept of white. But research methodology used was a qualitative methodology descriptive with informants the community inkecamatan gambiran. Background factors such as education socioeconomic, work, and economic conditions gives impact on the community in kecamatan gambiran in no respect voted (golput) during the election. Psychological factors and choice rational also affect them to stay in the election.In this case people still unconvinced against a candidate the head of the region or deputy head candidate regions, because they consider janji-janji on during the campaign not realized when power they have them and policies be given away from a satisfactory. This is what makes people not voted (golput) during the election last Keywords: Evaluation, election, voted.